2022
DOI: 10.3389/fcvm.2022.933913
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index as a potential biomarker of cardiovascular diseases: A systematic review and meta-analysis

Abstract: BackgroundSeveral studies have investigated the value of the systemic immune-inflammation index (SII) for predicting cardiovascular disease (CVD), but the results were inconsistent. Therefore, a meta-analysis and systematic review were conducted to assess the correlation between SII and risk of CVD.Materials and methodsTwo investigators systematically searched PubMed, Embase, Web of Science, Cochrane library, and CINAHL databases to identify all studies that examined the association between SII levels and CVD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 56 publications
4
47
0
1
Order By: Relevance
“…When determined by other comorbidities, a significant relationship was noted between SII and hypertension in p. pustular patients (p < 0.05), while smoking, diabetes and others were non-significant. This result is consistent with previous studies that demonstrated association between psoriasis and cardiovascular diseases [26] [27], however, it is the first study to show an association between SII and a cardiovascular disease in p. pustular as a subtype of psoriasis. Looking at our study as a whole, there appears to be a relationship between SII and p. pustular whereas no relationship exists with p. vulgaris and p. erythroderma.…”
Section: Discussionsupporting
confidence: 93%
“…When determined by other comorbidities, a significant relationship was noted between SII and hypertension in p. pustular patients (p < 0.05), while smoking, diabetes and others were non-significant. This result is consistent with previous studies that demonstrated association between psoriasis and cardiovascular diseases [26] [27], however, it is the first study to show an association between SII and a cardiovascular disease in p. pustular as a subtype of psoriasis. Looking at our study as a whole, there appears to be a relationship between SII and p. pustular whereas no relationship exists with p. vulgaris and p. erythroderma.…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to differences in the population and suggests that the changing trend of blood lipids is different in different inflammatory diseases. In recent years, many studies have confirmed the predictive efficacy of the SII index in cardiovascular disease [34][35][36][37][38], and a recent meta-analysis also showed that people with high SII index levels have a significantly increased risk of CVD [39]. The SII index value also increased significantly at different CVD initiations.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, many studies have confirmed the predictive efficacy of the SII index in cardiovascular disease [ 34 38 ], and a recent meta-analysis also showed that people with high SII index levels have a significantly increased risk of CVD [ 39 ]. The SII index value also increased significantly at different CVD initiations.…”
Section: Discussionmentioning
confidence: 99%
“…SII is considered to be able to comprehensively evaluate the level of immunity and inflammation status. In a meta-analysis involving 152,996 patients, higher SII was associated with an increased risk of nearly all CVD subtypes, including myocardial infarction, ischemic or hemorrhagic stroke, and peripheral arterial disease ( 27 ). Basic research has also confirmed the involvement of SII components in hypertension.…”
Section: Discussionmentioning
confidence: 99%